Automated Energy Optimization of HTTP Requests for Mobile Applications - Ding Li; Yingjun Lyu; Jiaping Gui; Halfond, William G. J. (Proceedings / International Conference on Software Engineering, 2016)
Energy is a critical resource for apps that run on mobile devices. Among all operations, making HTTP requests is one of the most energy consuming. Previous studies have shown that bundling smaller HTTP requests into a single larger HTTP request can be an effective way to improve energy efficiency of network communication, but have not defined an automated way to detect when apps can be bundled nor to transform the apps to do this bundling. In this paper we propose an approach to reduce the energy consumption of HTTP requests in Android apps by automatically detecting and then bundling multiple HTTP requests. Our approach first detects HTTP requests that can be bundled using static analysis, then uses a proxy based technique to bundle HTTP requests at runtime. We evaluated our approach on a set of real world marketplace Android apps. In this evaluation, our approach achieved an average energy reduction of 15% for the subject apps and did not impose a significant runtime overhead on the optimized apps.